2005
DOI: 10.2165/00126839-200506060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacology of Bilastine,??a New Selective Histamine??H1 ??Receptor Antagonist

Abstract: These preclinical studies provide evidence that bilastine has H1- antihistamine activity, with high specificity for H1-receptors, and poor or no affinity for other receptors. Bilastine has also been shown to have anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 5 publications
4
63
0
2
Order By: Relevance
“…The efficacy of bilastine is supported by preclinical studies in vitro and in experimental animals in vivo showing bilastine to be a potent H 1 -antihistamine [12,13]. It is also supported by a study of 525 patients with chronic idiopathic urticaria in which 20 mg of bilastine once daily was of similar efficacy to 5 mg levocetirizine [14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The efficacy of bilastine is supported by preclinical studies in vitro and in experimental animals in vivo showing bilastine to be a potent H 1 -antihistamine [12,13]. It is also supported by a study of 525 patients with chronic idiopathic urticaria in which 20 mg of bilastine once daily was of similar efficacy to 5 mg levocetirizine [14].…”
Section: Discussionmentioning
confidence: 92%
“…In vitro studies [12] have shown bilastine to have moderate to high affinity and potent activity at the histamine H 1 -receptor while having negligible affinity or effects at 30 different receptors including serotonin, bradykinin, LTD 4 , calcium, muscarinic, a 1 , b 2 , H 2 , H 3 and H 4 receptors. These results are supported by in-vivo studies in experimental animals [13] which also showed bilastine to be rapidly absorbed following oral dosing and to have a long duration of action.…”
Section: Introductionmentioning
confidence: 99%
“…Both cetirizine and fexofenadine are well established in the treatment of allergic rhinitis [7,8] while bilastine is a newly developed drug. Preclinical studies have shown that bilastine is a potent H 1 -antihistamine with a high selectivity for H 1 -receptors and poor or no affinity for other receptors, including serotonin, bradykinin, leukotriene-D 4 , muscarinic M 3 -receptors, a 1 -adrenoceptors, b 2 -adrenoceptors, and H 2 -and H 3 -histamine receptors [9]. By use of the Shultz-Dale reaction, bilastine has also been shown to have anti-inflammatory properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that bilastine is a potent H 1 -antihistamine with a high selectivity for H 1 -receptors and poor or no affinity for other receptors, including serotonin, bradykinin, leukotriene-D 4 , muscarinic M 3 -receptors, a 1 -adrenoceptors, b 2 -adrenoceptors, and H 2 -and H 3 -histamine receptors [9]. By use of the Shultz-Dale reaction, bilastine has also been shown to have anti-inflammatory properties [9]. In clinical studies, bilastine has been shown to have a rapid onset of action and a long duration of effect [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…None of the conducted clinical trials showed any influence of bilastine on the morphology of the ECG signal and QTc interval. Thus, it could be stated that the cardiovascular safety of bilastine is very high, and the influence of the drug on morphology of the ECG signal and cardiac muscle repolarization is the same as that of placebo [10,15,[32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Cardiovascular Safety Of Antihistaminesmentioning
confidence: 99%